Trends and factors associated with pneumonia mortality at Buea Regional Hospital in Cameroon from 2020 to 2023 - Kukwah Anthony Tufon; Tiayah Patience Foumene; Malika Esembeson; Ayah Flora Bolimo; Tiayah Precious Yemene; Chapajong Mariecole Nguatem; Teuwafeu Denis Georges; Ronald Mbua Gobina; Nkouonlack Cyrille; Tiayah Munge; Ngomba Divine Martin Mokake (PLoS ONE, 2025)
Background Pneumonia cases and associated deaths remain a public health concern necessitating ongoing efforts in prevention, diagnosis, and treatment. This study was aimed at identifying the trend of pneumonia, case fatality rate and factors associated with pneumonia mortality at the Buea regional hospital from 2020 to 2023. Methods In this retrospective study, data was collected from all available and complete adult inpatient/outpatient hospital records from 2020 to 2023 at Buea regional hospital. Only patients clinically and radiologically diagnosed with pneumonia (excluding TB and COVID-19) were considered for this study. Data was analyzed using SPSS with statistical significance set at p < 0.05. Results After reviewing 18,805 entries/records, 746 files corresponding to 746 patients (59.5% females) diagnosed with pneumonia were retained with mean age of 54.7 ± 19.2 years. There was a fluctuating trend in cases across the years with 2021 generally having higher values. There was a decreasing trend in case fatality rate across the years (2020: 17%, 2021:24%, 2022:8%, 2023:6%) with an overall case fatality rate of 13.7%. Being hospitalized for ≤10 days (aOR: 10.14, CI: 2.31–44.52, p = 0.002) and not being treated with amoxicillin-clavulanic acid (aOR: 3.33, CI: 1.43–7.75, p = 0.005) were significantly associated with pneumonia mortality. Conclusion Although the number of pneumonia cases fluctuated over time, they remained consistently present across all months from 2020 to 2023, highlighting the year-round nature of pneumonia transmission and its endemicity in the Buea Health District. Being hospitalized for less than 10 days and not using amoxicillin-clavulanic acid for treatment were risk factors of pneumonia mortality. These findings underscore the importance of timely diagnosis and empiric treatment with guideline recommended agents such as amoxicillin–clavulanic acid so as to reduce pneumonia mortality in the Buea regional hospital.